The Influence of the Principal's Academic Supervision and School Climate on the Performance of Public Middle School Teachers - Murti, Meri Kristina; Suanto, Elfis; Futra, Dedi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
Teacher performance is something that needs and deserves to be examined in depth. Many factors cause problems related to teacher performance. This article will cover the influence of the principal's academic supervision and school climate on the performance of state middle school teachers. This research uses a quantitative-descriptive approach. This quantitative descriptive research systematically, actually, and accurately describes certain social phenomena, with the aim of describing in detail the existing facts and data. Data collection techniques use observation, documentation, and questionnaires. The subjects of the research were 76 teachers at state middle schools. The results of the research show that: 1) The principal's academic supervision has a significant positive influence on teacher performance, with a significance value of 0.022 or smaller than the alpha value of 0.05. 2) School climate has a significant positive influence on teacher performance, with a significance value of 0.000. 3) The principal's academic supervision and school climate jointly influence teacher performance, with a significance value of 0.000 and an R-Square value of 0.590 indicating that the proportion of influence of the principal's academic supervision variable and school climate on the teacher performance variable is 59.0%.